KEPEMIMPINAN NON MUSLIM DALAM TAFSIR AL-MISBAH KARYA M. QURAISH SHIHAB - Munawir Munawir (Fakultas Ushuluddin Adab dan Humaniora (FUAH), Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto, 2017)
Non-Muslim leadership becomes a problematic issue in the context of inter-religious relations in Indonesia, especially for Muslims in conducting religious-social-political relations with non-Muslims. The problematic position of this non-Muslim leadership issue is the state constitution allows but the religious constitution (based on the textuality of the Qur'an) forbids. How does M. Quraish Shihab respond as well as answer the problematic of the people in the case? It is this core issue that will be tested by the answer through this research. Using the descriptive-inferential method and the philosophical-historical approach (philosophical and historical approach), the conclusion that M. Quraish Shihab in interpreting the verses (ban) of non-Muslim leadership (Surat al-Maidah: 51, QS Ali 'Imran: 28, and QS al-Mumtahanah: 1) is contextual, or in other words, the verses are understood to be sociological and not theological. Therefore he allows non-Muslim leadership as long as the non-Muslims are not of a hostile group of Islam, even he does not allow the leadership of a Muslim if a Muslim is actually injurious Islam and harms the interests of Muslims.